Relatório de Estágio Profissional "À Procura do Profissional do Ensino no Ensino Profissional" - José Maria Toscano Pessoa Ramos Pinheiro (2018)
This report aims to share, in a well-founded and critical way, the experience of a trainee student (the author) facing the professional reality for the first time and trying to illustrate the successes and failures that have contributed to the consistent development of the fundamental teaching skills. The professional internship took place in a Basic and Secondary Education School of a municipality in Porto and it was made up by three student trainees, the Cooperating Teacher of the school and the Faculty Advisor. This report is organized into six main chapters, the first being the Introduction of the report. The second chapter is about the Personal Dimension and it encompasses the autobiographical view of the personal, academic, professional and sporting career that contributed to the choice not only of this master's degree but also of all the progress already made regarding Sports. Besides this, it also refers to the expectations created for this practicum. The third chapter mentions the Framework of Professional Practice and the legal, institutional and functional context in which the practicum occurred. The fourth chapter is focused on the Professional Practice with reference to teaching-learning process, participation in the school life and relationship with the community. Chapter five consists of a short essay on Professional Courses. The Conclusion and Perspectives for the Future is presented in the sixth chapter. It emphasizes the importance of personal and professional development during the internship, making a final balance and providing a perspective for the professional future.